The LKB1–AMPK Signaling Axis Modulates Ferroptosis in Fibroblast-Like Synoviocytes Derived from Rheumatoid Arthritis - Ha-Reum Lee; Su-Jin Yoo; Jinhyun Kim; Seong Wook Kang (Biomedicines, 2025)
Background/Objectives: Ferroptosis is a type of regulated cell death that involves iron-dependent accumulation of lipid peroxides. Because fibroblast-like synoviocytes (FLSs) in patients with rheumatoid arthritis (RA) have a hyperplastic and inflammatory phenotype, selective induction of FLS cell death is considered a potential treatment strategy for RA. Liver kinase B1 (LKB1)-activated AMP-activated protein kinase (AMPK) signaling regulates the inflammation and migration of RA FLSs, contributing to RA pathogenesis. Here, we aimed to determine the effect of LKB1 knockdown on the ferroptosis pathway in RA FLSs. Methods: Synovial tissues from patients with RA (n = 5) were transfected with siRNA targeting LKB1. Cell viability was evaluated via 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide (MTT) assay and Annexin V/7-aminoactinomycin D (7-AAD) staining. Ferroptosis was assessed using boron-dipyrromethene (BODIPY) lipid probes, a ferrous ion detection kit, and a glutathione detection assay. Expression of hallmarks of various cell death pathways was analyzed using western blot. Results: RA FLS cell death significantly increased after transfection with LKB1 siRNA (p < 0.01). Lipid peroxidation was upregulated and the expression levels of glutathione peroxidase 4 (GPX4) and solute carrier family 7 member 11 (SLC7A11) were suppressed in LKB1-deficient cells. Additionally, LKB1 inhibition made RA FLSs highly sensitive to ferroptosis. When RA FLSs were incubated with an activator of AMPK, LKB1 knockdown-mediated inhibition was restored through upregulated expression of GPX4 and SLC7A11. Conclusions: these findings suggest that LKB1–AMPK signaling is essential to protect RA FLSs against ferroptosis.